Employment of Entry-Level Journalists- Case of Georgia - Gersamia, Mariam; Maia Toradze , (European Journal of Multidisciplinary Studies, 2018)
The purpose of this research is to identify the common criteria (knowledge and skill-based competences) which employers consider in the process of employing young journalists. The research holds significance for adjusting educational programs and accreditation standards. This research answers the following questions: 1. According to what criteria are entry-level journalists employed in Georgia? 2. What specific knowledge and skills are more attractive for employers? 3. Do employers take into consideration what University was attended, specific qualifications and earned degrees? Employers from 25 media organizations answered questionnaires (with close and open-ended questions). According to the results, only 40 percent of interns are paid in Georgia. While employing journalists "writing and editing skills" (88 percent) are the most important ones. Employers consider that “meeting deadlines” and an ability to work with new technologies are important skills as well (76 percent). 52 percent of employers prioritize a profound knowledge of a specific field (besides journalism). It is worth mentioning that 84 percent of respondents give preference to the competences gained in specific fields such as economy, politics, arts, etc. According to employers’ opinion, journalists gain more theoretical knowledge than practical at universities. For the majority of employers, practical knowledge is more essential. According to survey results, the specific recommendations have been produced for the media educational sector.
Keywords: Employment, Entry-Level Journalists, Georgia, media education